Effect of welding processes on microstructural and mechanical properties of dissimilar weldments between conventional austenitic and high nitrogen austenitic stainless steels. (January 2017) - Vashishtha, Himanshu; Taiwade, Ravindra V.; Sharma, Sumitra; Patil, Awanikumar P.
Abstract: High nitrogen austenitic stainless steels are in great demand due to their outstanding combination of strength and ductility, excellent work-hardening capability and corrosion resistance at relatively cost-effective than conventional stainless steels. The replacement compatibility of most widely used conventional austenitic stainless steel (type 304) was investigated by employing dissimilar weldments with high nitrogen austenitic stainless steel (type 201) using scanning electron microscope coupled with EDS and X-ray diffraction techniques. Dissimilar weldments between conventional and high nitrogen stainless steel was prepared using gas tungsten arc welding and shielded metal arc welding processes. The weld defects and their integrity were investigated by radiographic analysis. The effect of welding speeds on microstructural characteristics and grain boundary precipitation was analyzed. The subsequent effect on mechanical properties was studied using tensile test and microhardness evaluation. The faster cooling rate associated with higher welding speed resulted in 5% increment in ultimate tensile strength for GTAW process and 9% for SMAW process respectively.